How islamic finance is resilient during the pandemic - Shafitri Arindya Ramadhanty; Liliana Inggrit Wijaya; Putu Anom Mahadwartha (Universitas Hayam Wuruk Perbanas, 2022)
During the pandemic, Islamic fnance showed good resilience and contributed to the country’s economy. However, few studies are trying to discover the underlying factors of Indonesia’s Islamic fnance resilience and the appropriate measures to achieve sustainability in Indonesia’s Islamic fnance. Therefore, the purpose is to fnd the underlying factors of Islamic fnance’s resilience in Indonesia during the pandemic and discover what makes Islamic fnance in Indonesia sustainable. After analyzing the data using Straus’ grounded theory coding, the fndings indicate that the ﬂexible structure of Islamic fnance becomes the main factor contributing to the resilience and sustainability of Islamic fnance in Indonesia during the pandemic. Other factors such as a variety of “akad” and government agenda also contribute to its resilience and sustainability during the COVID-19 pandemic. Further, Indonesia’s government and Islamic fnancial institutions must develop quality human capital and adapt to technological changes. Lastly, it is hoped that this study could contribute to the development of Islamic fnance in Indonesia.